The communicative and organisational competencies of the librarian in networked learning support: a comparative analysis of the roles of the facilitator and the librarian. - Trine Schreiber; Camilla Moring (Information Research: An International Electronic Journal)
The aim of the paper is to compare the role of the facilitator with the role of the librarian. Firstly, a list of the role dimensions of the facilitation is described. Secondly, a case study of a facilitation proces is presented. Thirdly, the intermediary functions of the librarian is considered. The comparison shows that the similarities between the two roles concerns the communication, the identification of information needs and the translation of the user formulations into a systematized terminology. Moreover, we cannot exclude that two elements of the librarian's information seeking process; i.e., the searching activity and the evaluation of the results, may exist in the work of the facilitator. Still, the important difference is, that the information seeking process, carried out of the facilitator, may be based not on the information needs of the user but on the predetermined outcome of the communication process. However, a more explicit work with the functions of the librarian; i.e.. both the searching activity and the evaluation of the results, during a networked communication process, may strengthen the group understanding development. In this way, the role of the librarian could develop the role of the facilitator. At the same time, the attention of the facilitator to the needs of the group could bring an important aspect into the role of the librarian.